2018
DOI: 10.1103/physrevb.98.155102
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of the square-lattice Heisenberg model

Abstract: Despite nearly a century of study of the S = 1/2 Heisenberg model on the square lattice, there is still disagreement on the nature of its high-energy excitations. By tuning toward the Heisenberg model from the exactly soluble Ising limit, we find that the strongly attractive magnon interactions of the latter naturally account for a number of spectral features of the Heisenberg model. This claim is backed up both numerically and analytically. Using the density matrix renormalization group method, we obtain the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 59 publications
7
33
0
Order By: Relevance
“…Regarding the nature of the excitations around (π, 0), which we discuss in (Sec. III B 3), several theories have been proposed, such as an interaction between the magnon and a double spinon mode [29,30,32] or a repulsion from continua of multimagnon (bound) states [23]. We indeed observe a dip in the magnon energy, increasing with bond dimension, in agreement with earlier iPEPS results [9].…”
Section: Dispersionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the nature of the excitations around (π, 0), which we discuss in (Sec. III B 3), several theories have been proposed, such as an interaction between the magnon and a double spinon mode [29,30,32] or a repulsion from continua of multimagnon (bound) states [23]. We indeed observe a dip in the magnon energy, increasing with bond dimension, in agreement with earlier iPEPS results [9].…”
Section: Dispersionsupporting
confidence: 91%
“…A recent study [23], which used time evolution of semiinfinite cylindrical systems to obtain the dynamical structure factor, proposed a simple description of the excitation nature at the M point; by moving away from the isotropic point of the Hamiltonian, i.e., λ < 1 in (20), where the case λ = 0 corresponds to the Ising limit. It was observed that for small λ three distinct types of resonances in the transverse structure factor could be identified: an isolated single magnon branch, three-magnon bound states, and combinations of a magnon and a two-magnon bound state.…”
Section: Nature Of Excitations At (π 0)mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the key features that allows us to perform machine learning of the regular-to-chaos transition is the difference in statistical properties of |ψ n | 2 in the two regimes. While in the chaotic case the wavefunctions have Gaussian statistics, in regular case the probability distribution is non-universal and has a power-law singularity at small values of ψ n [36].…”
mentioning
confidence: 99%